سلطة الادارة العامة في مكافحة التلوث الضوضائي - الشريفي, بدر زيد كمر (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Noise pollution is one of the most prominent forms of environmental pollution emerging in the modern era. It has become a real threat to the lives, mental and physical health of individuals, and negatively impacts their peace and daily stability. With the increase in noise resulting from industrial development, urban expansion, and the proliferation of transportation, this phenomenon has become a matter of increasing concern at the national and international levels. This has necessitated the intervention of public authorities to mitigate its negative effects. This requires the intervention of the executive authority, in particular, to implement relevant laws, utilizing the powers and means at its disposal to maintain public order and its various components, including public security, health, and public tranquillity. Since noise pollution constitutes a disruption to both health and public tranquillity, it is imperative that the administration take action to combat noise pollution and mitigate its effects.